Kinship and History in South Asia Four Lectures - Trautmann, Thomas R. (Michigan Papers On South And Southeast Asia, 2020)
Kinship and History in South Asia presents four papers given at a small conference of kinship studies scholars, "Kinship and History in South Asia," at the University of Toronto in 1973. They draw upon one another and show several common concerns, particularly the theoretical importance of Dravidian systems. Yey they remain specialist studies, each within its own raison d'être. Brendra E. F. Beck contributes a study of the "kinship nucleus" in Tamil folklore, Levi-Straussian both in its treatment of kinship and of mythology. George L. Hart's study of woman and the sacred in the ancient Tamil literature of the Sangam attempts to elucidate this literature in its own terms, and also to relate it to Beck's "kinship nucleus." Thomas R. Trautmann presents a critical examination of the evidence for cross-cousin marriage in early North India, attempting to determine historical fact from literary materials. Narendra K. Wagle offers a survey of the kinship categories to be found in the Pali Jatakas.